Lipoic Acid Conjugated Boron Hybrids Enhance Wound Healing and Antimicrobial Processes - Hasan Türkez; Özge Çağlar Yıldırım; Sena Öner; Abdurrahim Kadı; Abdulkadir Mete; Mehmet Enes Arslan; İrfan Oğuz Şahin; Ömer Erkan Yapça; Adil Mardinoğlu (MDPI AG, 2022)
Complications of chronic non-healing wounds led to the emergence of nanotechnology-based therapies to enhance healing, facilitate tissue repair, and prevent wound-related complications like infections. Here, we design alpha lipoic acid (ALA) conjugated hexagonal boron nitride (hBN) and boron carbide (B4C) nanoparticles (NPs) to enhance wound healing in human dermal fibroblast (HDFa) cell culture and characterize its antimicrobial properties against Staphylococcus aureus (S. aureus, gram positive) and Escherichia coli (E. coli, gram negative) bacterial strains. ALA molecules are integrated onto hBN and C4B NPs through esterification procedure, and molecular characterizations are performed by using transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and UV-vis spectroscopy. Wound healing and antimicrobial properties are investigated via the use of cell viability assays, scratch test, oxidative stress, and antimicrobial activity assays. Based on our analysis, we observe that ALA-conjugated hBN NPs have the highest wound-healing feature and antimicrobial activity compared to ALA-B4C. On the other hand, hBN, ALA-B4C, and ALA compounds showed promising regenerative and antimicrobial properties. Also, we find that ALA conjugation enhances wound healing and antimicrobial potency of hBN and B4C NPs. We conclude that the ALA-hBN conjugate is a potential candidate to stimulate regeneration process for injuries.